2021
DOI: 10.1002/pen.25814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of α‐cellulose as a green filler on physico‐mechanical properties of a solution grade styrene‐butadiene rubber based tire‐tread compound

Abstract: Physico-mechanical and dynamic mechanical properties of typical solution grade styrene-butadiene rubber (S-SBR) and polybutadiene rubber (PBR) based tiretread compound were investigated by partially replacing highly dispersible (HD) silica with naturally occurring α-cellulose. Fourier transform infrared spectrum detected abundance of hydroxyl group in α-cellulose, which has created keenness to investigate its reinforcement characteristics in an S-SBR and PBR based compound. Scanning electron microscope and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…[ 12,13 ] The development of such reinforcing systems using high aspect ratio nanofillers along with low‐cost fillers like carbon black can be of huge technical significance in the rubber or tire industries. [ 14–16 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12,13 ] The development of such reinforcing systems using high aspect ratio nanofillers along with low‐cost fillers like carbon black can be of huge technical significance in the rubber or tire industries. [ 14–16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The development of such reinforcing systems using high aspect ratio nanofillers along with low-cost fillers like carbon black can be of huge technical significance in the rubber or tire industries. [14][15][16] The viscoelastic responses of polymer nanocomposites are very important from both the processing and application point of view. The viscoelastic characteristics of polymer nanocomposites can be attributed to the existence of two main factors: the neat or free polymer matrix whose hydrodynamic effects are unaffected by filler incorporation, and a three-dimensional network formed of either interconnected fillers or fractions of polymer adsorbed filler.…”
Section: Introductionmentioning
confidence: 99%
“…The large quantity of α‐cellulose can be potentially used for the production of paper. It has been stated that there is a relationship with the content of α‐cellulose and various properties such as thermal stability, molecular weight and crystallinity, in general, when it is used as a filler 131,132 . In this context, Nieschlag et al 124 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been stated that there is a relationship with the content of α-cellulose and various properties such as thermal stability, molecular weight and crystallinity, in general, when it is used as a filler. 131,132 In this context, Nieschlag et al 124 demonstrated that percentages higher than 34.0% are appropriated for these purposes. Thus, the SW as agro-industrial residues, treated through the GM, can be suitable for the production of pulp and paper.…”
Section: Polymorphous Identification and Compositional Phase Quantifi...mentioning
confidence: 99%
“…Additionally, some examples are described in more detail in Table 8. Other studies also used BR [170][171][172], SR [173][174][175][176][177], EPDM [178,179] and EVA [180], as well as rubber blends such as NR/SBR [181][182][183][184][185][186], NR/NBR [187], NR/SBR/BR [188,189], NR/BR [190], NR/EVA [191] and SBR/NBR [192] as a matrix for lignocellulosic-based rubber composites.…”
Section: Synthetic Rubbersmentioning
confidence: 99%